Unmeasured costs of haemophilia: the economic burden on families with children with haemophilia. (8th May 2015) - Price, V. E.; Hawes, S. A.; Bouchard, A.; Vaughan, A.; Jarock, C.; Kuhle, S.
<x xml:space="preserve">Abstract</x> Introduction and objectives Although economic evaluations of haemophilia‐related care have highlighted both the health care payer and societal perspectives, the costs to families with children with haemophilia have not been examined. This study determined the costs incurred by families of children with haemophilia, attending a haemophilia treatment centre (HTC), servicing a large geographical area in Eastern Canada. Methods Families recorded all direct and indirect costs associated with haemophilia‐related care for a year. Costs incurred to receive care at the HTC and local health care centres were compared. The relationship between distance to the HTC and costs was modelled using linear regression. Results Participants included 31/45 children (68%) from 27 families attending the HTC. Median age was 12 years (range: 0.5–17 years); 24/31 (77%) had severe haemophilia. The median distance to the HTC and local health care facility was 230 km (range: 7–600 km) and 33.5 km (range: 2–400 km) respectively. Due to this difference in distance, 23/31 (74%) children do not attend the HTC for management of acute haemorrhage. The median annual total cost per family to attend the HTC is $775.93 (range: $200.00–$5741.00). The total cost to attend the HTC increases by $2.16 (95% CI 1.24–3.9) per kilometer from the HTC. The median total annual cost of haemophilia‐related care per family is $1222.50 (range: $396.00–$8037.00). Conclusion Families incur high costs related to haemophilia care. The distance to the HTC is a barrier to care. Improving access to HTCs is paramount in improving haemophilia‐related outcomes.